Translation Competence and Market-oriented Translator Training in a Globalized World - Huangfu, Wei (Advances in Social Sciences Research Journal, 2018)
Higher Education translator training programs have to keep in pace with market changes and students’ expectation in a globalized world. Based on (European Master’s in Translation)EMT’s competence framework and European Union’s EN 15038 classifications of translator competences, this study is to propose a specialized translators’ training mode, which can be designed and implemented in a learner-centered and market-oriented curriculum. Provided in this paper is the detailed illustrations of the procedures for the related translation process and teaching focus to tap students’ self-management potentials, and encourage group work and use of technical tools. This study aims to contribute to the improvement of the pedagogy in translator training by suggesting the procedures or strategies in translator training, and by serving as a reference source for future training programs.